'Mutations from Below': The Land Raiders of Reef and An Sùileachan (2013) by Will Maclean and Marian Leven. Issue 2 (November 2020) - Blair, Lindsay
Abstract : The focus of this paper is the memorial structure, An Sùileachan, at Uig on the Island of Lewis which was designed by Will Maclean and Marian Leven and built by stonemasons Ian Smith and James Crawford in 2013. The memorial, dedicated to the Land Raiders of Reef, is the fourth in a series of memorial sculptures to commemorate the struggles of the people against landlord control in different communities on the Island of Lewis. The title for this paper 'Mutations from Below' is used by Michel Foucault in his radical re-interpretation of classification systems, The Order of Things. Much of Foucault's writing is concerned with power relations, the way that power is exercised over people's freedom. The democratic thrust of Foucault's writings is paralleled in the determination of the artists, Maclean and Leven, to give a voice to the unrepresented voices of the people of Reef at the time of the Land Raid in 1913 and more generally to the voices of the people in their opposition to their treatment at the hands of landowners and their factors during the Clearances. In successive stages of the essay, the insights of different cultural theorists – Martin Heidegger, Gianni Vattimo, Mikhail Bakhtin, and Jacques Rancière – help to ground the argument in philosophical exegesis. Finally, the paper seeks to determine the nature and extent of the connection between the political and the aesthetic within the memorial sculptural form as exemplified at An Sùileachan.